Untersuchungen zum Rückgang der kleinbäuerlichen Grundnahrungsmittelproduktion in ausgewählten Munizipien des nordostbrasilianischen Agreste - Rheker, Johannes R. (ERDKUNDE, 1989)
Since colonial times, the undulated, very heterogeneous Agreste Region must be regarded as the most important food-supplier for the population of north-east Brazil. There is, however, much evidence that the traditional production of staple-food (especially beans and maize), which is mostly carried out by smallholders, has recently suffered from strong declines in some parts of the region. Studies in eight selected Agreste-communities (municipios) prove that the causes for this decline vary considerably. Thus, not only the expansion of other economic activities (cattle breeding, cultivation of fruits and vegetables, textile industry), but also irregularities within the precipitation regime, as well as shortcomings in the supply of credits and seeds are, in various intensities, responsible for the displacement or impairment of the traditional staple-food production.